POSISI DAN PERANAN STRATEGIS PENGAJARAN IPA (FISIKA) DI SLTP - Mundilarto Mundilarto (Jurnal Cakrawala Pendidikan, 2002)
It is felt that the availability ofhigh quality human resourceshas become an urgent needinrelation to the challenges that wouldbe faced by the Indonesian nation in times to come.Thejuniorhigh school is a partofthe nine-year basic schooling which is the required minimum education for all Indonesians.Therefore, the position and roleofthe teaching ofthe physicalsciences there in the courseof developing human resources isextremely strategic. For a numberofits graduates, the juniorhighschool is the last partoftheir formal education. After graduating,they generally choose working rather thari continuing their schooling. Meanwhile, a partofthose who can continue their schoolingmay enter the fieldof the social sciences, a field which is nolonger related to the physical sciences.In relation with the mission that the junior high school bears,the basic knowledge and skills students learn there should beflexibly useful for both future work and further study. Therefore,the teachingofthe physical sciences at junior high school shouldbe c.onducted accordingly efficiently and effectively.